The Hidden Diet: Determining the Distribution of the Threatened Julia Creek Dunnart (Sminthopsis douglasi) Using Eastern Barn Owl (Tyto javanica delicatula) Pellets - Dana A. Lockhart; Joshua J. Bon; Cameron L. Charley; Stephen G. Kearney; Pia Schoenefuss; Emma L. Gray; Andrew M. Baker (Ecology and Evolution)
ABSTRACT Approximately 30% of the world's biodiversity has been threatened or driven to extinction since the 1500s, with Australia losing 10% of its endemic terrestrial mammal species in the last 200 years. The Julia Creek dunnart (Sminthopsis douglasi) is a threatened small mammal endemic to Queensland (Australia) that requires monitoring and protection. However, there is insufficient ecological data to determine its distribution adequately, and the species has only been sporadically caught in live trapping surveys, with no population size estimates. In the present study, eastern barn owl (Tyto javanica delicatula) pellet analysis was used to assess a range of locations for the presence of the Julia Creek dunnart as a prey species. Owl pellet deposit sites were chosen to encompass areas of high, medium, and low likelihood of Julia Creek dunnart occurrence based on Australian Government habitat models for the species with the goal of better understanding the species' distribution. In the analysis, Julia Creek dunnarts were present at four (of nine) locations, including all high‐likelihood locations, half of the medium‐likelihood locations, and no low‐likelihood locations. This result supported the accuracy of the Australian Government habitat models. Results also demonstrated the importance of the long‐haired rat (Rattus villosissimus) in the eastern barn owl diet during plague years. The research will assist with prioritizing sites for protection and monitoring of the Julia Creek dunnart. It also adds support to the utility of owl pellet analysis alongside or independent of traditional surveying techniques, such as live trapping, when targeting cryptic small mammal species.